The Role of Citizens’ Suggestions in a Policy Process – A Case Study of Long Power Outages in Finland - Kinnunen, Markku (Scandinavian Journal of Public Administration, 2019)
This paper examines the role of citizens in the process of preparing an energy policy to improve security of supply in an electricity network. It describes a real-life case of thepolicy formulation stage of a policy cycle. This study describes citizens’ suggestions on how to secure electricity networks against severe weather conditions and the role these suggestions played in policy formulation. The data was collected through a citizen surveyand by interviewing civil servants. The citizens’ suggestions were analysed using inductive qualitative content analysis and the interview data was summarised in detail.The results indicate that the citizens’ suggestions did not provide any new answers to thetechnical problem of how to prevent long power outages, and they were not utilised in the policy formulation. However, the citizen survey was part of crisis management during and after the long power outages. We conclude by discussing the degree to whichcitizens’ suggestions are useful for the authorities and distribution system operators in a wider context, as well as the lessons learned from citizen participation.